Al-Marzouqi, Abu Yaʿrab. “The Philosophy of the Philosophical Translation and the Conditions of Civilizational Creativity in its Symbolic and Real Dimensions,” Year 11, Issue 41 (Summer 1426 AH/ 2005 CE), Pp. 89-140. - المرزوقي أبو يعرب (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2005)
Abu Yaʿrab al-Marzouqi’s study attempts to comprehend the conditions of philosophical translation: experimentally through treatment of certain models, and theoretically by studying statements that are culturally particular and statements that are normative. His study consists of three main issues: an applied attempt to identify artificial obstacles in translation; an attempt to treat the nature of the obstacles faced by translation; and the comprehensive conditions of continuity from a Qur’anic perspective. The study then contends that all that is arrived at by the human mind in terms of solutions is captured within the aims of Islam.